Candida species extracellular alcohols: production and effect in sessile cells - Martins, Margarida Isabel Barros Coelho (2010)
Cell-cell signaling alcohol molecules were recently identified in Candida albicans and Candida dubliniensis supernatants. To date, it is not known whether these molecules are produced by other Candida species and their role in biofilm formation is not fully clarified. Herein, Candida parapsilosis and Candida tropicalis extracellular alcohols production by planktonic cultures was analyzed by headspace-solid-phase microextraction and gas chromatography-mass spectrometry. Both these Candida species extracellular media contained E,E-farnesol, 1-dodecanol, 2-phenylethanol, and isoamyl alcohol but not E-nerolidol, as produced by C. albicans and C. dubliniensis. Moreover, the ability of these compounds to regulate C. albicans, C. dubliniensis, C. parapsilosis, and C. tropicalis sessile cells was assessed by adding the alcohols after 3 h of adhesion and 48 h of biofilm formation. After 24 h, biofilms were analyzed in terms of cellular mitochondrial activity and total biomass. E,E-Farnesol affected C. albicans and C. dubliniensis. E-Nerolidol and 1-dodecanol elicited C. parapsilosis and C. tropicalis changes in further biofilm development. C. tropicalis was affected by 2-phenylethanol and isoamyl alcohol triggered changes in C. albicans, C. dubliniensis, and C. tropicalis sessile cells. The results demonstrated that almost all of these alcohols are produced by these Candida species and also evidence the complexity of biofilm formation.